ANALISIS KONTRIBUSI PENDAPATAN ASLI DAERAH (PAD) TERHADAP KEMANDIRIAN DAERAH KABUPATEN/KOTA DI NUSA TENGGARA BARAT 2011-2018 - Muchlisin Danu Wardana; Abdul Wahid Mahsuni; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the effect of the contribution of Regional Taxes, Regional Levies, Management of Separated Regional Assets, and other legitimate Original Regional Revenue (PAD) simultaneously and partially on District/City Financial Independence in West Nusa Tenggara. This research uses quantitative research. The research data is in the form of data previously collected and has become the documentation of the West Nusa Tenggara Regional Revenue Agency. The sample used in this research is the PAD Realization Report and the District/City Budget Realization Report in West Nusa Tenggara from 2011 to 2018. Data were analyzed statistically using SPSS for Windows v.22.0. The results of the analysis show the significance value of testing data on Regional Taxes, Regional Levies, Management of Separated Regional Assets, other legitimate PAD and Regional Financial Independence, respectively, are ,826, ,711, ,682, ,246, ,928. Based on results of the research, this can be concluded that partially Regional Taxes and other Legitimate Original Regional Income have a significant effect on Regional Independence. Meanwhile, Regional Levies and Management of Separated Regional Assets do not have a significant effect on Regional Independence. Meanwhile, Local Taxes, Regional Levies, Management of Separated Regional Assets and other PAD simultaneously have a significant influence on Regional Independence.Keywords: local taxes, regional levies, regional independence.